ANALISIS YURIDIS KEABSAHAN KESEPAKATAN MELALUI SURAT ELEKTRONIK (E-MAIL) BERDASARKAN HUKUM INDONESIA - GLENN BIONDI (PREMISE LAW JURNAL, 2016)
Agreement is one of the requirements for a contract. The use of e-mail as the media for an agreement has the impact on the international society in general and the Indonesia people in particular. For the Indonesian people, this is related to an important legal problem either it is viewed from it’s validity according to the prevailing legal provisions in Indonesia or from the settlement of the dispute which is caused by the agreement through e-mail. The objective of the research was to find out the validity of a contract through e-mail, the use of digital signature, and how about the settlement of dispute caused by a contract through email. The research used judicial normative method and it’s specification was done by using descriptive analytic approach. The source and the type of the data were secondary data. The data were gathered by using library research and analyzed qualitatively. Keywords: Agreement, Digital Signature, E-mail